Cytokines Stimulate the Release of Microvesicles from Myeloid Cells Independently from the P2X7 Receptor/Acid Sphingomyelinase Pathway - Colombo, Federico; Bastoni, Mattia; Nigro, Annamaria; Podini, Paola; Finardi, Annamaria; Casella, Giacomo; Ramesh, Menon; Farina, Cinthia; Verderio, Claudia; Furlan, Roberto (Frontiers in Immunology, 2018)
Microvesicles (MVs) are membrane particles of 200-500 nm released by all cell types constitutively. MVs of myeloid origin are found increased in the cerebrospinal fluid of patients suffering from neuroinflammatory disorders, although the factors triggering their production have never been defined. Here, we report that both pro- and anti-inflammatory cytokines, specifically interferon-and interleukin-4, are equally able to stimulate the production of MVs from microglia cells and monocytes. Additionally we found this process to be independent from the best characterized molecular pathway so far described for membrane shedding, which is centred on the purinergic receptor P2X7, whose activation by high concentrations of extracellular ATP results in membrane blebbing operated by the secreted enzyme acid sphingomyelinase. Moreover, a potent inhibitor of acid sphingomyelinase, injected in a mouse model of multiple sclerosis, failed to reduce the number of MVs in their CSF. This suggests that cytokines, rather than extracellular ATP, may exert a long-term control of MV production in the context of chronic inflammation, where both pro- and anti-inflammatory factors play coordinated roles.